ANALYSIS OF BASE SUBSECTORS AND LEADING AGRICULTURAL COMMODITIES IN SEKADAU REGENCY, WEST KALIMANTAN PROVINCE - R, Hernovianty F; B, Soeryamassoeka S; Komala, Erwan; Elsa, Mukti Tri; Erni, Yuniarti (Jurnal Teknik Sipil, 2022)
The contribution of agriculture which has increased each year has been encouraged to be a strategic area for the economic development of Sekadau Regency. However, weakness of planning policy, insufficient quantity, and quality of infrastructure are obstacles to developing strategic areas. This study aims to analyze the basis of sub-sectors and leading commodities of agriculture in Sekadau Regency. The research approach used an exploratory qualitative with descriptive analysis methods to get an overview of agricultural productivity and Location Quotient Analysis, Shift-Share Analysis, and Klassen Typology to get the leading commodities of agriculture. The results of the study show that the productivity level of the agricultural sub-sector in Sekadau Regency is quite diverse. The agricultural and progressive sub-sector in Sekadau Regency is owned by food crops and plantations. Furthermore, the leading commodities of the food crop sub-sector in Sekadau Regency are corn, rice, and sweet potatoes. The main commodities of plantation sub-sectors in Sekadau Regency are pepper, rubber, and oil palm.